2014
DOI: 10.1080/01457632.2014.888920
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Oxyfuel and Air–Fuel Combustion in an Industrial Water Tube Boiler

Abstract: The characteristics of oxyfuel combustion are compared to those of air-fuel combustion in the furnace of a typical industrial water tube boiler. Two oxyfuel cases are considered. These correspond to 21% O 2 and 29% O 2 by volume. Validations for both oxyfuel combustion and air-fuel combustion indicate that the temperature levels are reduced in oxyfuel combustion. The results show that, as the percentage of recirculated CO 2 is increased, the temperature levels are greatly reduced. It is concluded that the flam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…From a combustion perspective, there are also some challenges in the pathway of successful adoption of the oxy-combustion technology. The greater CO 2 concentration within the combustor (∼70% by mass) reduces the chemical kinetic rates, which, in turn, reduce the laminar burning velocity , as well as the combustion efficiency, , as compared to air combustion. The CO 2 -rich oxy-fuel premixed reactant mixture requires more oxygen (above 21%) than the corresponding air combustion system operating at the same equivalence ratio, to obtain a stable flame. , In a comparative numerical study of a porous combustor, it has been reported that oxy-combustion with an oxygen fraction of 30% by volume can yield an adiabatic flame temperature similar to that of air combustion under identical operating conditions .…”
Section: Oxidizer-flexible Combustionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a combustion perspective, there are also some challenges in the pathway of successful adoption of the oxy-combustion technology. The greater CO 2 concentration within the combustor (∼70% by mass) reduces the chemical kinetic rates, which, in turn, reduce the laminar burning velocity , as well as the combustion efficiency, , as compared to air combustion. The CO 2 -rich oxy-fuel premixed reactant mixture requires more oxygen (above 21%) than the corresponding air combustion system operating at the same equivalence ratio, to obtain a stable flame. , In a comparative numerical study of a porous combustor, it has been reported that oxy-combustion with an oxygen fraction of 30% by volume can yield an adiabatic flame temperature similar to that of air combustion under identical operating conditions .…”
Section: Oxidizer-flexible Combustionmentioning
confidence: 99%
“…Lastly, transported CO 2 can be stored safely in geographical rock deep beneath the surface of the Earth, in depleted oil fields for enhanced oil recovery processes, or in deep saline aquifers. Capturing CO 2 can be performed by three methods, pre-, post-, and oxy-fuel combustion. In the pre-combustion technique, CO 2 is partly captured by converting the fuel into syngas before going into the combustion zone. The post-combustion technique captures CO 2 from the exhaust gas after the combustion process, through absorption, adsorption, membrane separation, or cryogenic processes. The use of air as an oxidizer (air combustion) is, however, not beneficial from a carbon-capture perspective, because unreacted nitrogen from air forms the primary constituent of GT exhaust, which reduces the CO 2 concentration in it, thus complicating the CO 2 separation process and increasing the associated costs of carbon capture.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Since boilers and industrial furnaces are one of the largest consumers of fossil fuels, optimization and retrofitting these facilities are of the most essential tasks that can be done to reduce fuel consumption and pollutant emission into the environment. 2,[9][10][11] Therefore, in order to evaluate the operation condition of oilfield heating furnace more accurately, it is necessary to carry out the numerical simulation technology study, which can lay a foundation for the realization of the national energy conservation and emission reduction binding goals.…”
Section: Introductionmentioning
confidence: 99%
“…The CO/CO 2 concentration in conventional coal‐fired boiler is 95% higher than oxy‐fuel combustion with NO x emission reported to have reduced by a one‐third as a result of use of oxy‐fuel combustion . A comparison of oxy‐fuel, with nitrogen replaced by carbon dioxide, to air‐fuel combustion shows a reduced temperature levels and a slower fuel consumption in the oxy‐fuel combustion system . Pure oxygen required for oxy‐fuel combustion is produced by the cryogenic air separation technology which has been reported to be expensive and thermodynamically inefficient .…”
Section: Introductionmentioning
confidence: 99%
“…Oxy-fuel combustion is gradually gaining attention especially because of its of zero-emission potential [2] and its applicability to solid, liquid and gaseous fuel. In oxy-combustion of methane gas, CH 4 reacts with the O 2 to give a product of CO 2 + H 2 O. The CO 2 is captured after condensation of steam in a simple cooling process.…”
Section: Introductionmentioning
confidence: 99%